Reticular telangiectatic erythema from implanted devices attributed to low‐grade infection with Staphylococcus epidermidis. Issue 1 (15th February 2019) - Wuyts, Laura; Van Dyck, Frederic; Kamerling, Niels; Olyslaegers, Christophe; Jansens, Hilde; Lambert, Julien; Aerts, Olivier
Abstract: Reticular telangiectatic erythema (RTE) is a poorly defined clinical condition occurring days, months to even years after the implantation of medical devices such as orthopaedic prostheses, neurostimulators and pacemakers. In its pathogenesis a role for Staphylococcus epidermidis has been suggested, but such cases have only rarely been reported. We describe three patients, one with a neurostimulator and two with an orthopaedic prosthesis, respectively, in whom a RTE developed and, ultimately, could be attributed to a low‐grade infection with the biofilm‐producing S. epidermidis . The devices showed no apparent technical defects and patch tests, to exclude a contact‐allergic origin of the RTE, were negative in all cases. However, an antimicrobial strategy, including antibiotic therapy and removal of the infected devices, led to complete disappearance of the RTE in all cases. The subsequent and uneventful replacement by a new, but identical, medical device, in two of three patients, further argues for a potential aetiologic role of S. epidermidis in the occurrence of some cases of—otherwise unexplained—RTE.